2020
DOI: 10.1186/s12939-020-1123-y
|View full text |Cite
|
Sign up to set email alerts
|

Too poor or too far? Partitioning the variability of hospital-based childbirth by poverty and travel time in Kenya, Malawi, Nigeria and Tanzania

Abstract: Background: In sub-Saharan Africa, women are most likely to receive skilled and adequate childbirth care in hospital settings, yet the use of hospital for childbirth is low and inequitable. The poorest and those living furthest away from a hospital are most affected. But the relative contribution of poverty and travel time is convoluted, since hospitals are often located in wealthier urban places and are scarcer in poorer remote area. This study aims to partition the variability in hospital-based childbirth by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…When both cost-friction surface approach and OSRM were compared previously, larger discrepancies were reported for long travel time estimates. 36 …”
Section: Discussionmentioning
confidence: 99%
“…When both cost-friction surface approach and OSRM were compared previously, larger discrepancies were reported for long travel time estimates. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Some similar studies in resource limited settings have cited distance to the facilities [35] or unavailability of health services to be associated with lower HSB amongst the rural populations [36]. A multi‐country study conducted in SSA shows that people in Malawi took the least time to their nearest health facility compared to other countries [37]. However, amongst the rural populations, access to local health centres or hospitals is often constrained by a lack of transport and inability to meet the direct and indirect costs of a clinic visit [29].…”
Section: Discussionmentioning
confidence: 99%
“…Striving to reach the health-related SDG 3 targets for maternal and child health outcomes depends on progress in eliminating poverty de ned in SDG 1 (3). Studies in other parts of Ethiopia (26,27) and elsewhere (3,28) have documented similar ndings. The respondents suggested a way forward: initiating communitybased self-funding schemes, such as a green bank, i.e., contributing cereals every harvesting season to support the poor.…”
Section: Discussionmentioning
confidence: 84%
“…In our study, poor women, far away from health facilities, were found to utilize less services. Physical accessibility is associated with the utilization of services (28,31). Thus, emphasis should be given to strengthening the community-and home-based activities and expanding local maternal and child health services as suggested by the respondents.…”
Section: Discussionmentioning
confidence: 99%